2011
DOI: 10.1007/s10637-011-9734-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-neoplastic agent thymoquinone induces degradation of α and β tubulin proteins in human cancer cells without affecting their level in normal human fibroblasts

Abstract: The microtubule-targeting agents derived from natural products, such as vinca-alkaloids and taxanes are an important family of efficient anti-cancer drugs with therapeutic benefits in both haematological and solid tumors. These drugs interfere with the assembly of microtubules of α/β tubulin heterodimers without altering their expression level. The aim of the present study was to investigate the effect of thymoquinone (TQ), a natural product present in black cumin seed oil known to exhibit putative anti-cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 43 publications
4
37
0
2
Order By: Relevance
“…We also found that growth of normal human astrocytes is not affected by concentrations of TQ that are cytotoxic to glioblastoma cells. This is in agreement with previous reports showing that TQ is selective for cancer cells [24], [25], [54]. It is important to note that TQ readily crosses the blood brain barrier: in mouse models of petit mal epilepsy, TQ administered by intraperitoneal injection was shown to delay the onset and decrease the duration of seizures [26], and in rat models of ischemia-induced brain injury, TQ administered in drinking water prevented the depletion of several crucial endogenous neuronal antioxidants [27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that growth of normal human astrocytes is not affected by concentrations of TQ that are cytotoxic to glioblastoma cells. This is in agreement with previous reports showing that TQ is selective for cancer cells [24], [25], [54]. It is important to note that TQ readily crosses the blood brain barrier: in mouse models of petit mal epilepsy, TQ administered by intraperitoneal injection was shown to delay the onset and decrease the duration of seizures [26], and in rat models of ischemia-induced brain injury, TQ administered in drinking water prevented the depletion of several crucial endogenous neuronal antioxidants [27].…”
Section: Discussionsupporting
confidence: 92%
“…It is known that microtubule poisons, such as paclitaxel and vincristine, are capable of inducing LMP [38], [44], [57] and interfering with lysosomal trafficking [59]. TQ was recently demonstrated to target microtubules, causing a time and dose-dependent degradation of α and β-tubulin in U87MG glioblastoma and Jurkat T lymphoblastic leukemia cells [54]. Taken together, these reports support our findings that TQ induces LMP and cathepsin translocation in glioblastoma cells.…”
Section: Discussionsupporting
confidence: 87%
“…After treatment, cells were washed twice with PBS and then lysed in TRIS buffer containing protease inhibitors (5 μg/mL leupeptin, 5 m m benzamidine) and 2% Triton ® X‐100 on ice. Total proteins (30 μg) were separated by electrophoresis on 10% SDS‐polyacrylamide (Sigma) gels as previously described . Blotting membranes were incubated with the primary mouse antibody for p‐IκBα (US Biological, Swampscott, MA, USA; 1:1000 dilution) or total IκBα (Millipore, Molsheim, France, 1:1000 dilution) overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Das and collaborators [100] showed that thymoquinone and diosgenin, alone and in combination, inhibited cell proliferation and induced apoptosis in squamous cell carcinoma. Alhosin and collaborators [101] demonstrated that thymoquinone induced degradation of α - and β -tubulin proteins in human cancer cells without affecting their levels in normal human fibroblasts.…”
Section: Introductionmentioning
confidence: 99%